Inflammatory myofibroblastic tumor causing intestinal obstruction in older adults due to intestinal intussusception: Case report - Montes-Arcón, Pablo Salomón (2023)
Intestinal intussusception in adult patients is a rare entity, which corresponds to about 5% of all causes of intestinal obstruction, its diagnosis is not easy given the lack of specific symptoms of patients who present it. This is mainly based on the findings of imaging studies, surgical management is the cornerstone of treatment of this pathology and its success will be determined by timely diagnosis as well as by the expertise of the treating surgeon. This article presents the case of a 62-year-old male patient who consults due to nonspecific abdominal pain and irritative urinary symptoms, who due to persistence of abdominal pain despite medical management is taken to surgery where it is diagnosed intraoperatively. an intestinal intussusception at the level of the distal ileum.